Comparative Analysis of the Ethiopian and Kenyan Detention Systems - Zsiga, Nikoletta Evelin (Journal of Central and Eastern European African Studies, 2025)
Colonialism brought extensive suffering to Africans. One of its manifestations was the operation of concentration camps and detention camps in Italian-occupied Ethiopia and British-controlled Kenya. In both colonies, European powers faced resistance: in Ethiopia, an assassination attempt targeted the Italians, while in Kenya, the Mau Mau movement –primarily composed of Kikuyu people – rose up against British rule. To suppress these resistance efforts, concentration camps and detention facilities were established, where thousands of Africans lost their lives. This paper seeks to answer, among other questions, the following: What conflicts led to establishing concentration camps in the colonies under discussion, and what purpose did they serve? The compara¬tive analysis focuses on the conditions in the camps, the treatment of internees, and the resulting mortality figures.